A Study on Problems at Primary Health Centres in Coimbatore District - Dharshinivishnupriya , B.; Velmurugan , Dr.R. (International Journal of Accounting and Economics Studies, 2025)
Primary Health Centres (PHCs) act as the primary healthcare foundationwhich provides essential medical services at prices that people can afford to rural communities across India. The operational capabilities of Primary Health Centres face multiple important barriers that lead to decreased medical quality delivery and substandard patient health benefits. Patient experience data support that PHC faces primary difficulties from staffing issues and staff shortages, together with medical supply problems and financial deficits and facility limitations, and poor diagnostic methods. Special care needs of overcrowded conditions with long waiting queues, short clinics, and insufficient patient transfer systems, and dirty facilities, and lack of emergency medical treatment create a compound problem. The analysis discovered that healthcare delivery faces two types of issues: administrative hurdles coexist with interpersonal problems that include medical corruption and improper treatments, along with deficient healthcare education and communication problems. The patient reported challenges organized into three main dimensions through factor analysisprovided an acceptable explanation of their issues. The findings show that proper intervention programs need to merge solutions for multiple health problems with operational enhancements to produce better outcomes for marginalized patient populations. The discovery of new information functions as a foundation to launch pivotal public policy movements that benefit primary healthcare structures and additional academic research initiatives to identify system enhancement strategies. This investigation aims to fill some of the gaps identified above by analyzing the PHC system's operational inefficiencies from an economic perspective, focusing specifically on the cost of chronic PHC medicine shortages and the understaffing of primary health care centers. Such financial burdens exacerbate impoverished low-income households’ health and economic welfare simultaneously.
Keywords: Primary Health Centres (PHCs); Healthcare Accessibility; Patient Challenges; Operational Inefficiencies and Healthcare Quality